2017
DOI: 10.1155/2017/2969064
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Ocular Blood Flow Shown by Laser Speckle Flowgraphy, Retinal Arteriosclerotic Change, and Chorioretinal Circulation Time Obtained by Fluorescein Angiography

Abstract: Purpose. To determine the correlations among the mean blur rate (MBR) in the optic nerve head (ONH) shown by laser speckle flowgraphy (LSFG), retinal arteriosclerosis, and the circulation time obtained by fluorescein angiography (FA). Method. We evaluated 118 patients and assessed their time of choroidal flush, arm-to-retina time, and early and late phases of retinal circulation time (RT: sec) obtained by FA. The severity of retinal arteriosclerosis was classified according to the Scheie classification. The MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…In RVO eyes, there is a significant association between vascular MBR and early-and late-phase fluorescein angiography circulation times. 4 Similarly, two studies found a significantly lower blood flow in the ONH in ischemic RVO compared to nonischemic RVO, matching our understanding of severe perfusion deficits in eyes with ischemic RVOs. 24,25 LSFG findings also match our understanding of retinal autoregulation, because pure oxygen inhalation significantly decreases ONH MBR in healthy eyes.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…In RVO eyes, there is a significant association between vascular MBR and early-and late-phase fluorescein angiography circulation times. 4 Similarly, two studies found a significantly lower blood flow in the ONH in ischemic RVO compared to nonischemic RVO, matching our understanding of severe perfusion deficits in eyes with ischemic RVOs. 24,25 LSFG findings also match our understanding of retinal autoregulation, because pure oxygen inhalation significantly decreases ONH MBR in healthy eyes.…”
Section: Introductionmentioning
confidence: 64%
“…Recently, imaging techniques such as laser speckle flowgraphy (LSFG) and OCT angiography (OCTA) have emerged as more-precise and lessinvasive ways of determining changes in retinal blood flow. 4,5 LSFG, approved by the Food and Drug Administration in 2016, is a relatively new, noninvasive technology for measuring retinal blood flow. [6][7][8][9] Although other imaging techniques exist, such as blue-field simulation, spectral-domain OCT, laser Doppler flowmetry, laser Doppler velocimetry, Doppler Fourier-domain OCT, and swept source OCT, LSFG is unique in that it is a noninvasive technique that allows for quantitative, dynamic imaging of blood flow through retinal vessels and the choroid in the optic nerve head (ONH) and macula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ophthalmologists previously reported evaluation of ocular blood flow with LSFG, 912 and one vascular surgeon reported determination of leg blood flow using this method. 6 All of these studies used the value itself; the former used the MBR only to monitor individual changes, while the latter used BSSP itself to distinguish between non-PAD controls and PAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Laser speckle flowgraphy (LSFG) can be used to determine cutaneous blood flow without making contact with the skin. 68 There have been several reports of the evaluation of ocular blood flow with LSFG, 9–13 but there has been only one report of the use of this method to determine cutaneous blood flow in the leg. 6…”
Section: Introductionmentioning
confidence: 99%